Dampak Pandemi Covid-19 terhadap Proses Pemenuhan Kewajiban Perpajakan oleh Wajib Pajak yang Terdaftar pada Kantor Pelayanan Pajak (KPP) Pratama Pontianak Tahun 2020 - Sari Zawitri; Ninik Kurniasih; Wida Arindya Sari (Jurusan Akuntansi Politeknik Negeri Pontianak, 2021)
The purpose of this research is to see the impact on tax revenue, and the impact on out in tax reporting KPP Pratama in Pontianak in the pandemic covid 19. The research is a case study of exploration and researches the mixing of qualitative and quantitative methods. The kind of data that was used was the data as primary and secondary data. The technique of the data collection was done in 3 ways: 1. Interview, 2. Documentation, and 3. A method of the literature study. Then sample based on the achievement of the depth and wealth a description of, not the total sample. Analysis technique that produces the thematic analysis answer the interviews and of identification and reporting the data from the payment of tax like both of persons private and the tax year 2019. The result showed (1) research first showed that Covid-19 fulfillment of obligations would not have an impact on both the taxpayers and the person in the pay taxes on income tax PPh and PPN (tax) they increase in value. (2) the results of research second related fulfillment of an obligation related tax reporting SPT (announcement letter) an annual tax for the year 2019 declining tax effectively be 76 % or at the level of less docile, it is related to the development of the target the reporter threefold. The research is expected to push the government to optimize sources of certain tax revenue to offset the impact of tax revenue when pandemic Covid-19.